Pendidikan Informal Melaui Spiritualitas Alam dalam Novel Mata dan Rahasia Pulau Gapi Karya Okky Madasari - Muhammad Kriswanto; Muh. Fatoni Rohman (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2022)
Natural spirituality is the harmony of the human soul with nature in order to maintain and preserve the universe. It needs to be nurtured and strengthened in humans so as not to exalt destructive nature so that there is a need for nature-based education through literary forms in every child's growth process. The focus of this study is to describe the picture of natural spirituality and informal education through natural spirituality, which is constructed in the novel "Mata dan Rahasia Pulau Gapi" by Okky Madasari. The study uses a qualitative approach, text study methods, and literary ecology studies. Data collection uses reading and note-taking techniques. The data are in the form of narration, dialogue, or monologue. The results of this study: (a) the description of natural spirituality in the form of the nature of the centre of life, the realm of the reminder of death, the realm of spiritual reality, the nature of the source of life depicted in the characters of the novel; (b) the novel contains informal education through natural spirituality that fosters love, trust, and respect for the universe. It is a form of strengthening to eliminate the destructive nature that has damaged many universes.